Det goda seminariet: Om självständighet och lagarbete i den akademiska verkstaden - Cronqvist, Marie (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2014)
The research text seminar is generally a cherished element in academic life. Ideally, this is the place for the exchange of high intellectual thoughts in an atmosphere of mutual respect. But the text seminar, if viewed from the perspective of its historical roots in German academia, is also an arena for collective, informal and apprenticeship learning that is today challenged by a much more individualistic, formal and bureaucratic model for third cycle education. The seminar could be seen as what Etienne Wenger has called a “community of practice” in which we learn our trade and whose qualities we need to safeguard.